2018
DOI: 10.1002/jlb.3ab0518-178r
|View full text |Cite
|
Sign up to set email alerts
|

Roles for T/B lymphocytes and ILC2s in experimental chronic obstructive pulmonary disease

Abstract: Pulmonary inflammation in chronic obstructive pulmonary disease (COPD) is characterized by both innate and adaptive immune responses; however, their specific roles in the pathogenesis of COPD are unclear. Therefore, we investigated the roles of T and B lymphocytes and group 2 innate lymphoid cells (ILC2s) in airway inflammation and remodelling, and lung function in an experimental model of COPD using mice that specifically lack these cells (Rag1−/− and Rorafl/flIl7rCre [ILC2‐deficient] mice). Wild‐type (WT) C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 52 publications
7
63
0
Order By: Relevance
“…[18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a).…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttp supporting
confidence: 72%
See 4 more Smart Citations
“…[18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a).…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttp supporting
confidence: 72%
“…We previously showed that mice develop small airway remodelling characterised by increases in collagen deposition, epithelial cell area and numbers of nuclei around and in the small airways in experimental COPD. [18][19][20][21][22][23] As expected, chronic CS exposure of wild-type mice increased collagen deposition around the airways compared to normal air-exposed wild-type controls (Figure 3a). CS-exposed Zfp36 aa/aa mice were protected against collagen deposition with no differences compared to normal air-exposed Zfp36 aa/aa controls and had significantly reduced deposition compared to CS-exposed wild-type controls.…”
Section: Chronic Cs-induced Pulmonary Inflammation Is Reduced In Ttp supporting
confidence: 72%
See 3 more Smart Citations